Inhibition of monoamine oxidase by indole-5, 6-dicarbonitrile derivatives. Issue 6 (15th March 2015) - Chirkova, Zhanna V.; Kabanova, Mariya V.; Filimonov, Sergey I.; Abramov, Igor G.; Petzer, Anél; Petzer, Jacobus P.; Firgang, Sergey I.; Suponitsky, Kyrill Yu.
Graphical abstract: Abstract: Recent studies have found that phthalonitrile derivatives are remarkably potent inhibitors of human monoamine oxidase (MAO) A and B. In an attempt to further determine the structure-activity relationships (SARs) for MAO inhibition by this class of compounds and to discover novel potent MAO inhibitors, the present study investigated the MAO inhibition properties of a series consisting of indole‐5, 6‐dicarbonitrile derivatives. The results document that 3‐chloro‐1 H ‐indole‐5, 6‐dicarbonitrile derivatives exhibited potent inhibition of the MAOs. For example, 3‐chloro‐2‐(4‐methylphenyl)‐1 H ‐indole‐5, 6‐dicarbonitrile inhibited MAO-A and MAO-B with IC50 values of 0.014 μM and 0.017 μM, respectively. It was further shown that this compound acts as a reversible and competitive inhibitor of both MAO isoforms. An analysis of the SARs for MAO inhibition by 3‐chloro‐1 H ‐indole‐5, 6‐dicarbonitriles showed that methylation of the indole nitrogen eliminates MAO-B inhibition activity, and replacement of the 2-phenyl ring with the thienyl results in a 9-fold reduction of MAO-B inhibition activity. A series of 3‐bromo‐1-hydroxy‐1 H ‐indole‐5, 6‐dicarbonitriles are, in turn, comparatively weaker MAO inhibitors. It may be concluded that indole-5, 6-dicarbonitrile derivatives are suitable leads for the design MAO inhibitors for the treatment of disorders such as Parkinson's disease and depression.